2011
DOI: 10.1177/1066896911424899
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal (Undifferentiated) Sarcoma of the Liver With Peripheral Angiosarcoma Differentiation Arising in a Mesenchymal Hamartoma in an Adult Patient

Abstract: Embryonal (undifferentiated) sarcoma of the liver (ESL) is a rare malignant neoplasm composed of undifferentiated sarcomatous tissue. We are presenting a case of a 74-year-old woman diagnosed with an ESL arising from a mesenchymal hamartoma of the liver (MHL). Both lesions occur typically in childhood, with only rare reported cases in adults. Histologically, the mass consisted primarily of loose myxoid stroma admixed with bland spindle cells and extensive, cystic (lymphangioma-like) degeneration. However, also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Reports of UESL and angiosarcoma arising in HMH have been well documented [30][31][32][33][34][35]. Clinical and histological evidence has strongly suggested that UES can develop within a pre-existing HMH.…”
Section: Malignant Transformationmentioning
confidence: 99%
“…Reports of UESL and angiosarcoma arising in HMH have been well documented [30][31][32][33][34][35]. Clinical and histological evidence has strongly suggested that UES can develop within a pre-existing HMH.…”
Section: Malignant Transformationmentioning
confidence: 99%
“…Although mesenchymal hamartomas have a benign histological appearance, malignant transformation of nasal chondromesenchymal hamartoma (Li et al, 2013) and mesenchymal hamartoma of the liver (Ramanujam et al, 1999;Tucker et al, 2012) has been described. These cases emphasize the need for the complete removal of mesenchymal hamartoma and the need for long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although common in children between 6 and 10 years old, UES is very rare in adults over 60-years-old; for adults aged >60 years, only 14 UES cases have been reported in the world until now 3,4,5,6,7. UES was known to have no gender predominance in children, but there was female predominance (62.5%) in UES patients over the age of 30 worldwide 9.…”
Section: Discussionmentioning
confidence: 99%
“…This rare presentation is especially true for adults aged >60 years with only 14 cases of UES reported in this population until now 3,4,5,6,7. In Korea, eight cases of UES in adults have been reported: five cases were in women and four cases were in people older than 60 years 5,6,7,8.…”
mentioning
confidence: 91%